Impact of home quarantine due to COVID-19 among Bangladeshi population - S. M. Mustofa Kamal; Md. Feroz Kabir; Mohammad Habibur Rahman; Jalal Uddin; Md. Sujon Hosen; Shahida Sultana Shumi; Md. Ahnaf Al Mukit (International Journal of Public Health Science (IJPHS), 2021)
COVID-19 is an emergency public health issue and home quarantine can prevent the transmission. Quarantine restricts the people’s mobility and it has a silent impact on physical, psychological and economical aspect. The purpose was to explore the impact of home quarantine among the general population in Bangladesh. This was a descriptive type of cross sectional survey with 600 samples from different district of Bangladesh by convenient sampling with a structured and language validated questionnaire. The results indicate the huge impact of home quarantine. Among 600 participants, 71.7% (n=430) showed impact on their psychological health, 48.5% (n=291) physical health and 82.5% (n=495) on their economy. Study showed strong association between gender and psychological impact (p<0.01) and very strong association between living area and their psychological impact (p<0.00).There has also very strong association between their occupation and impact on their economy (p<0.00). Home quarantine has a progressive negative impact on the individual’s psychological health, physical health and their economy. Individual’s gender, living area and occupations are strongly associated with those negative impacts due to home quarantine. Supporting agency should take initiative to mitigate this all negative impacts of home quarantine and need to develop protocol for maintaining for health during quarantine time.